2016
DOI: 10.1016/j.msea.2015.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Superplasticity of a nano-grained Mg–Gd–Y–Zr alloy processed by high-pressure torsion

Abstract: While most of the reports on Mg-Gd-Y-Zr alloys report superplasticity after extrusion or friction stir processing, it is important to investigate superplasticity in these alloys after other severe plastic deformation processes having greater grain refinement capability. Accordingly, superplasticity was studied in an Mg-9Gd-4Y-0.4Zr (GW94) alloy after different high-pressure torsion (HPT) conditions. The HPT was performed at room temperature under an applied pressure of 6.0 GPa for up to 16 turns. TEM microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Also, there exists a saturation strain after which the grain refinement essentially ceases [38,39]. In an earlier investigation of Mg-Gd-Y-Zr alloys, it was found that the saturation strain of these alloys was ~4 corresponding to 4 passes of ECAP [24] and about ~72 corresponding to 8 turns of HPT [25] and therefore these optimum values were used in the present investigation.…”
Section: Grain Refinement By Extrusion Ecap and Hptmentioning
confidence: 94%
See 4 more Smart Citations
“…Also, there exists a saturation strain after which the grain refinement essentially ceases [38,39]. In an earlier investigation of Mg-Gd-Y-Zr alloys, it was found that the saturation strain of these alloys was ~4 corresponding to 4 passes of ECAP [24] and about ~72 corresponding to 8 turns of HPT [25] and therefore these optimum values were used in the present investigation.…”
Section: Grain Refinement By Extrusion Ecap and Hptmentioning
confidence: 94%
“…However, only limited reports are available to date documenting superplasticity in these alloys after processing by ECAP [23,24] or HPT [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations